Second Trimester Genetic Amniocentesis: Five- Year Experience of a Maternal- Fetal Medicine Unit - Orkun Çetin; Fatma Ferda Verit Atmaca; Ali Galip Zebitay; Ayşegül Deregözü; Begüm Aydoğan; Seda Keskin; Oğuz Yücel (Medical Network, 2016)
OBJECTİVE: The objective of this study is to identify the annual variations amniocentesis indications such as change in maternal age, cytogenetic results, and other indications. Another outcome is the investigation of the relationship between indications for amniocentesis and the distribution of chromosomal abnormalities. STUDY DESIGN: This study was designed as a retrospective analysis of amniocentesis results of the 1667 pregnant patients between January 2007 and December 2012 in the Süleymaniye Women's Health Education and Research Hospital. The karyotype results, indications for intervention and complications during procedure were reported. RESULTS: Total chromosome abnormalities were detected in 101 cases out of 1667 patients which correspond to a 6.1% of the total results. Distribution of the chromosomal abnormality detection rate with respect to the amniocentesis indication was 4.2%; in the abnormal first trimester screening tests group; 5.3% in the abnormal second trimester maternal serum screening group, 18.7% in the fetal malformations in previous pregnancy group, and 7.1%. in the abnormal ultrasound findings group. CONCLUSION: Amniocentesis is the most common invasive procedure for prenatal diagnosis. Although the advanced maternal age is still an important indication, there has been significant development of both new markers and technology making this indication for amniocentesis questionable. Prenatal ultrasonography for the soft markers of chromosomal aneuploidy in association with the maternal serum biochemical screening tests should be evaluated during the decision process for amniocentesis.